Clinical risk factors of carbohydrate antigen-125, cytokeratin fragment 19, and neuron-specific enolase in liver metastases from elderly lung cancer patients - Cheng, Tao; Chen, Jun; Ying, Ping; Wei, Hong; Shu, Huiye; Kang, Min; Zou, Jie; Ling, Qian; Liao, Xulin; Wang, Yixin; Shao, Yi (Frontiers in Genetics, 2022)
Objective: Lung cancer is a common malignant tumor characterized by challenging detection and lack of specificity in clinical manifestations. To investigate the correlation of tumor markers in the serum with liver metastasis and prognosis of lung cancer. Methods: A total of 3,046 elderly lung cancer patients were retrospectively studied between September 1999 and July 2020. Divided into liver metastasis group and non-liver metastasis group. We compared a series of serum biomarkers between the two groups of elderly patients, including tumor markers in the serum included alkaline phosphatase (ALP), serum calcium, hemoglobin (HB), alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cytokeratin fragment 19 (Cyfra21-1), carbohydrate antigen-125 (CA-125), carbohydrate antigen-153 (CA-153), carbohydrate antigen-199 (CA-199), and free prostate specific antigen (free PSA). We used binary logistic regression analysis to determine risk factors, and used receiver operating curve (ROC) analysis to evaluate the diagnostic value of liver metastases in elderly patients with lung cancer. Results: The proportion of lung cancer in the liver metastasis group was higher than that observed in the non-liver metastases group. The expression levels of CA-125, Cyfra21-1， and NSE in the liver metastasis group of lung cancer were significantly higher than those reported in the non-liver metastases group (P<0.05). ROC curve analysis shows that the area under the curve of CA-125, Cyfra21-1, and NSE are 0.614, 0.616 and 0.608, respectively. The sensitivity and specificity of CA-125 were 45.70% and 76.20%, the sensitivity and specificity of Cyfra21-1 were 60.10% and 57.10%, and the sensitivity and specificity of NSE were 44.10% and 75.00%, respectively. Conclusion: High levels of CA-125, Cyfra21-1, and NSE in the serum may be associated with liver metastasis in elderly patients with lung cancer. CA-125and NSE are factors influencing the prognosis of elderly patients with liver metastasis of lung cancer.